Dynamic Simulation Of Polymerization Reactor Python MMA Using - Kaventra, Gunasegaran (Universiti Sains Malaysia, 2021)
The colourless, volatile organic liquid methyl methacrylate (MMA) is utilised in the large-scale synthesis of poly-methyl methacrylate (PMMA) via a polymerization process. PMMA is widely utilised in construction, automobile parts, electronic devices, and medicinal applications. MMA polymerization reactor modelling and simulation was chosen as the study's subject of focus because it provides the automatic and dynamic analysis of output variables and trends for changes made in input variables as a function of time. Python programming language was used to create the MMA polymerization reactor simulator. Necessary extension libraries and modules were imported into Python to provide their respective functionality. Simulated data from Python and calculated data from Microsoft Excel were compared to each other and the mathematical model for MMA polymerization reactor simulator was validated with a low error percentage. The MMA polymerization reactor simulator was successfully created using Python and validated in terms of unsteady-state temperature at different time points. The impact of changes in input variables on reactor and jacket temperature was explored and seen by simulation in sensitivity and result analysis.